Legged Fire Fighter Robot Movement Using PID - Latif, Abdul; Shankar, K.; Thanh Nguyen, Phong (Journal of Robotics and Control (JRC), 2020)
Proportional Integral Derivative (PID) control is a control system commonly used by industry. Approximately 90% of industrial equipment uses a PID controller because it is easy to use. In the Indonesian Fire Extinguisher Robot Contest (IFERC), the contested robots must follow the contours of the walls of the arena. A Fire extinguisher robot navigation was chosen because the race arena of the competition consisted of walls with different aisles and rooms. The navigation robots used PID control. This study designed and implemented a control algorithm for legged fire extinguishing robots using the PID method, where the PID control was processed in a microcontroller. The angles for each servo motor generated by the calculation of the PID enable the robot to navigate by taking decisions to move quickly or slowly, turn right, turn left and stop. The robot's proximity sensor data and fire sensors enable the fire to be extinguished. The result showed that the robot can carry out its duties optimally.